O orçamento participativo na cidade de São Paulo - confrontos e enfrentamentos no circuito do poder - Dias, João Marcus Pires (2006)
The objective of this research is to explore in details the social and political challenges and confrontments observed during the participative government of Marta Suplicy mayor during 2001-2004. In this regard, the focus of this investigation is on the regional and sub-regional administration and insertion of public representation. In this context, this research examines how the municipal public administration and the population interacted, the consequent social implications and limits. Moreover, this study discusses the main conflicts and political relationships in several instances of the government, represented by the mayor cabinet and secretaries, the local government in the regional/sub-regional administrations, and popular representatives inserted in the Participative Budget PB). The methodology applied in the development of the present study consists of theoretical contributions and reflections about the subject, which comprise documents and previous references, field studies and data analysis, interview with technicians involved in the PB, as well as with leaders and representatives of the population at the preparatory and deliberative assembly